Genetic diversity of Brucella ovis isolates from Rio Grande do Sul, Brazil, by MLVA16 - Dorneles, Elaine MS (BioMed Central, 2014)
BACKGROUND: Ovine epididymitis is predominantly associated with Brucella ovis infection. Molecular characterization of Brucella spp. achieved by multi-locus variable number of tandem repeats (VNTR) analyses (MLVA) have proved to be a powerful tool for epidemiological trace-back studies. Thus, the aim of this study was to evaluate the genetic diversity of Brucella ovis isolates from Rio Grande do Sul State, Brazil, by MLVA16. FINDINGS: MLVA16 genotyping identified thirteen distinct genotypes and a Hunter-Gaston diversity index of 0.989 among the fourteen B. ovis genotyped strains. All B. ovis MLVA16 genotypes observed in the present study represented non-previously described profiles. Analyses of the eight conserved loci included in panel 1 (MLVA8) showed three different genotypes, two new and one already described for B. ovis isolates. Among ten B. ovis isolates from same herd only two strains had identical pattern, whereas the four isolates with no epidemiologic information exhibited a single MLVA16 pattern each. Analysis of minimal spanning tree, constructed using the fourteen B. ovis strains typed in this study together with all nineteen B. ovis MLVA16 genotypes available in the MLVAbank 2014, revealed the existence of two clearly distinct major clonal complexes. CONCLUSIONS: In conclusion, the results of the present study showed a high genetic diversity among B. ovis field isolates from Rio Grande do Sul State, Brazil, by MLVA16.